Systematic Literature Review: Application of Dynamic Geometry Software To Improve Mathematical Problem-Solving Skills - Susanto, Nabilla Calista Putri; Hartati, Sulis Janu; Standsyah, Rahmawati Erma (Universitas Wiralodra, 2023)
This study aims to review the literature on applying dynamic geometry software to improve mathematical problem-solving skills. The research method used is Systematic Literature Review (SLR), which includes planning, implementation, and reporting. Searching for articles using the Publish or Perish tool in the Google Scholar database. There were 100 articles found at the initial stage, with 15 that met the inclusion and exclusion benchmarks. The results of this study show that: 1). The Asian continent is the most widely used location in the application of dynamic geometry software, 2) Secondary school education level dominates research exposure, 3) Geogebra is the most widely used software in the application of dynamic geometry software to improve mathematical problem-solving, 4) The application of dynamic geometry software is dominated by Schoenfield's problem-solving theory where the use of software can meet five stages of problem-solving Schoenfield, i.e., reading, analysis, exploration, planning, implementation, and verification.